The people's victory how Malaysians saved their country - Kee, Thuan Chye (Marshall Cavendish Editions, 2019)
The Malaysian General Election (GE14) on 9 May 2018 resulted in a dramatic and decisive overthrow of the ruling government by the people of Malaysia. The People's Victory traces the story of Malaysia from the outcome of GE13 in May 2013, to the 1MDB exposé by the independent watchdog blog Sarawak Report and The Wall Street Journal in July 2015, and follows the dramatic events leading up to GE14 and the defeat of the ruling government on 9 May 2018. This book captures the full story of Malaysia from 2013 to 2018, including the intriguing twists and turns after the 9 May euphoria. It reveals various ironies as the story unfolds, such as Dr Mahathir Mohamad taking on the mantle of PM once more with a new mission to reform the country after having left it in a less than ideal state during his previous tenure; his formation of an alliance with the very man he sent to jail in 1998 on charges of sodomy and abuse of power; and obtaining Anwar Ibrahim a full pardon from the second sodomy charges for which he was convicted in 2015. This book tells of the rise of a new Malaysia, of Malaysians standing up for their principles, and taking responsibility for their own nation to achieve a true victory for the people.